Gas sensor based on ZnO film/silica pillars. (7th December 2016) - Liu, Jing; Liang, Yaxiang; Yi, Futing; Wang, Bo; Zhang, Tianchong; Wang, Yuting; Zhou, Yue
Abstract: Silica submicron pillars are used as substrate for Zinc oxide (ZnO) gas sensor for the first time. The submicron pillars with the large surface ratio can improve the gas sensing performance obviously. Silicon pillars are fabricated by cesium chloride (CsCl) self-assembly lithography and inductively coupled plasma dry etching as substrate, the ZnO film is deposited on the pillars surface by RF magnetron sputtering. With this method, the pillar based gas sensor has the higher gas response, the shorter response and recovery time than the planar one with different working temperatures, different gas concentrations. 300 °C is the best working temperature, for planar gas sensor, the gas response is 22.81 for 1520 ppm ethanol, the response time is 55 s and the recovery time is 169 s. While for the pillar based one, the gas response is 28.20, the response time is 51 s and the recovery time is 92 s.